Sulfur-Oxidizing Bacteria From Coal Mine Enhance Sulfur Nutrition in Pigeonpea (Cajanus cajan L.) - Malviya, Deepti; Varma, Ajit; Singh, Udai B.; Singh, Shailendra; Singh, Harsh V.; Saxena, Anil K. (Frontiers in Environmental Science, 2022)
The present investigation was carried out to isolate, identify and characterize sulfur oxidizing bacteria (SOB) from coal mines and to evaluate the efficient strains for their ability to influence plant growth and S uptake in pigeonpea. Thirteen bacterial isolates belonging to Stenotrophomonas maltophilia (2), Stenotrophomonas pavanii (2), Rhizobium pusense (5), Bacillus velezensis (2) and Paenibacillus massiliensis (2) were obtained. Among these, seven strains that could reduce the pH of thiosulfate broth were further characterized for sulfur oxidation, plant growth-promoting (PGP) attributes and in planta studies. Among the 7 strains characterized, maximum sulfate ion was recorded for S. maltophilia DRC-18-7A (311.43 mg L-1) closely followed by S. pavanii DRC-18-7B (273.44 mg L-1) and S. maltophilia DRC-18-10 (265.75 mg L-1) after 21 days of inoculation. Among the PGP attributes quantified, maximum P solubilization was recorded in case of S. maltophilia DRC-18-7A (24.39 µg ml-1), while highest siderophore production and IAA production were recorded in S. maltophilia DRC-18-10 (14.25%) and R. pusense DRC-18-25 (15.21 µg ml-1), respectively. S. maltophilia DRC-18-7A closely followed by S. pavanii DRC-18-7B outperformed others in enhancing seed germination (%) and vigour indices. Results clearly indicated that microbial inoculants colonized the plant roots and developed biofilm on root surface. It was further observed that plants treated with microbial inoculants induce an early formation of secondary and tertiary roots in the pigeonpea compared to the untreated control which was further confirmed by assessing the root architecture using the root scanner. Inoculation of these two strains to pigeonpea significantly enhanced plant growth parameters, the activity of reactive oxygen scavenging (ROS) enzymes and accumulation of flavonoids, carotenoids and proline both under sterilized and non-sterilized growth medium (sand and soil, 1:3 ratio). The application of microbial inoculants significantly increased the uptake of nitrogen, phosphorus, potassium and sulfur in plant shoots. Further, transcript level of phosphate, potassium and sulfur transporter genes significantly increase upon microbial inoculation led to increased uptake and translocation of P, K and S in the pigeonpea. The results indicate that S. maltophilia DRC-18-7A and S. pavanii DRC-18-7B could be recommended as inoculants for pigeonpea to improve its growth and sulfur nutrition.